2022
DOI: 10.3389/fnagi.2021.821336
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Glycated Hemoglobin Levels Are Associated With Poor Outcome in Acute Ischemic Stroke

Abstract: ObjectiveAdmission hyperglycemia is an established risk factor for functional outcome in patients with acute ischemic stroke. However, the association between glycated hemoglobin (HbA1c) and prognosis in patients with acute anterior circulation ischemic stroke (AACIS) remains controversial. This study aimed to explore whether elevated HbA1c levels are associated with functional outcome in AACIS patients.Participants and MethodsWe enrolled patients with AACIS hospitalized in the First Hospital Affiliated to Soo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Additionally, with rising HbA1c levels (HbA1c >8%), patients experience reduced functional independence. [18] The subgroup analysis based on baseline HbA1c levels between RE+TE10 and TE20 demonstrated a significant difference between two groups in HbA1c 9-9.9% subgroup (p=0.003), achieving HbA1c <7.5% with RE+TE10 at Week 16 from baseline, suggesting better outcomes for patients in this subgroup while for the other two subgroups (HbA1c 8-8.9% and 10-11%) difference was not statistically significant (Table 2). The reason of this findings could be the small no of patients in these subgroups.…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, with rising HbA1c levels (HbA1c >8%), patients experience reduced functional independence. [18] The subgroup analysis based on baseline HbA1c levels between RE+TE10 and TE20 demonstrated a significant difference between two groups in HbA1c 9-9.9% subgroup (p=0.003), achieving HbA1c <7.5% with RE+TE10 at Week 16 from baseline, suggesting better outcomes for patients in this subgroup while for the other two subgroups (HbA1c 8-8.9% and 10-11%) difference was not statistically significant (Table 2). The reason of this findings could be the small no of patients in these subgroups.…”
Section: Discussionmentioning
confidence: 89%
“…However, none of these studies have separately described the effects of HbA1c on ICLAD-related stroke. Nevertheless, the association between poor FOC and HbA1c >8% as compared to HbA1c ≤6.5% and 6.5 to ≤8% in patients with the LAA stroke subtype compared to those with the non-LAA type has been recently established by Dong et al ( 9 ). Similarly, Diprose et al reported that HbA1c is an independent predictor of poor outcomes following EVT.…”
Section: Discussionmentioning
confidence: 97%
“…Researchers from China have investigated the effect of admission HbA1c on functional outcomes (FOC) in AIS ( 7 9 ). Gao et al found HbA1c ≥6.7% to be associated with an unfavorable outcome in 793 patients with AIS due to small vessel occlusion ( 7 ), whereas Wang et al identified HbA1c ≥6.5% as an independent risk factor for adverse outcomes among 408 patients with AIS ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, brain tissue damage in ACI patients can cause dysregulation of the hindbrain-cardiac axis, stimulating increased production of cardiacderived BNP, which can further cause cardiac damage [18]. The following are possible explanations for the underlying mechanisms of the hindbrain-cardiac axis: HPA axis activation, sympathetic and parasympathetic regulation, catecholamine surge, dysregulation of the gut microbiota, immune response, and release of inflammatory particles and microRNAs [19,20]. BNP, Corin, and NEP are all important components of natriuretic peptides (NPs) [21,22].…”
Section: Discussionmentioning
confidence: 99%